Anemia and neutrophil‐to‐lymphocyte ratio in laryngeal cancer treated with induction chemotherapy. (22nd April 2019) - Gorphe, Philippe; Bouhir, Samia; Garcia, Gabriel C. T. E.; Alali, Abeer; Even, Caroline; Breuskin, Ingrid; Tao, Yungan; Janot, François; Bidault, François; Temam, Stéphane
Abstract : Objectives/Hypothesis: We studied the influence of the neutrophil‐to‐lymphocyte ratio (NLR) and anemia on the response to induction chemotherapy (IC) and survival outcomes in laryngeal cancer patients treated with a preservation protocol. Study Design: Retrospective single‐center case series. Methods: We analyzed patients with T3 laryngeal cancer treated with IC using a preservation protocol. The NLR and hemoglobin levels were assessed before treatment and after IC. The response to chemotherapy was assessed using Response Evaluation Criteria in Solid Tumours 1.1 and World Heath Organization standards. The oncological endpoints were overall survival (OS) and disease‐free survival (DFS). Results: Sixty‐eight patients were analyzed. The median NLR and hemoglobin levels before and after IC were 2.76 and 14.5 g/dL, and 2.01 and 11.6 g/dL, respectively. The NLR and anemia before treatment were not correlated, and they were not associated with the response to chemotherapy. However, an NLR > 5 and anemia before treatment were both associated with shorter OS and DFS. Notably, they were the only factors found to be significantly associated with survival outcomes. Conclusions: In laryngeal cancer, patients treated with a preservation protocol, a high NLR ratio, and anemia before IC were associated with shorter survival, independently of the response to chemotherapy. Level of Evidence: 4 Laryngoscope, 130:E144–E150, 2020